Evaluation of gas diffusivity models for no-tilled and tilled volcanic ash soils. Issue 9 (1st September 2016) - Guo, Linlin; Nishimura, Taku; Imoto, Hiromi; Sun, Zhigang
ABSTRACT: Accurate quantification of soil gas diffusion is essential to understand the gas transport mechanism in soils, especially for soil greenhouse gas emissions. To date, the performance of soil gas diffusivity ( D p / D 0, where D p is the soil gas diffusion coefficient and D 0 is the diffusion coefficient in free air) models has seldom been evaluated for no-tilled and tilled volcanic ash soils. In the present study, six commonly used models were evaluated for volcanic ash soils under two treatments by comparing the predicted and measured soil gas diffusivities at water potentials of pF 1.3–3. The Buckingham-Burdine-Campbell (BBC), soil-water-characteristic-dependent (SWC-dependent), and two-region extended Archie's Law (2EAL) models showed better performance for both no-tilled and tilled volcanic ash soils, which is likely because porosity and pore size parameters of bimodal soils were taken into consideration in these models. Since the BBC model showed better accuracy than the SWC-dependent and 2EAL models and required fewer, more easily measurable parameters, this study recommends the BBC model for predicting soil gas diffusivity of volcanic ash soil under different tillage managements. In future studies, the BBC model should be further tested at water potentials of pF > 3, and may be improved by including the parameters of pore continuity and saturation.